1996
DOI: 10.4315/0362-028x-59.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora and Aflatoxin-Producing Strains of Aspergillus flavus in Greenhouse-Cultivated Green Beans (Phaseolus vulgaris L.)

Abstract: The fungal contamination in green beans (Phaseolus vulgaris L.) was studied according to their location and height during growth in greenhouses. The genera most frequently isolated were Aureobasidium, Aspergillus, Penicillium, and Alternaria. Height and location did not have a significant influence on the fungal contamination of the beans. A strain of A. flavus was isolated which had the capacity to synthesize aflatoxins in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings are comparable to those of Ruiz et al (1996) in Argentina, who found that Aspergillus spp. and Penicillium spp.…”
Section: Extraction Yieldsupporting
confidence: 89%
“…These findings are comparable to those of Ruiz et al (1996) in Argentina, who found that Aspergillus spp. and Penicillium spp.…”
Section: Extraction Yieldsupporting
confidence: 89%
“…Of these fungi, Alternaria alternata, Ascochyta spp., Colletotrichum spp., Fusarium spp., and Macrophomina phaseolina were the most frequent and common pathogens of these crops. Alternaria, Aspergillus, Curvularia, Drechslera, Eurotium, Fusarium, Penicillium, Rhizoctonia, Mucor, Rhizopus, Sclerotium, and Gliocladium were the most common fungal genera isolated from various legume seeds (Tseng et al 1995;Ruiz et al 1996;El-Nagerabi and Elshafie 2000;Kritzinger et al 2003;Castillo et al 2004;Kumar et al 2004;Domijan et al 2005;Embaby and Abdel-Galil 2006;Attitalla et al 2010). Fusarium, Penicillium, Rhizopus, Cladosporium and Alternaria were the main seedborne pathogens on the surface of five major seeds of leguminous plants from Ningxia, China (Liu et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The Alternaria, Aspergillus, Curvularia, Drechslera, Eurotium, Fusarium, Mucor, Penicillium, Rhizoctonia, Rhizopus, Sclerotium, and Gliocladium were the most common fungal genera isolated from different legume seeds: broad bean (Vicia faba), kidney bean (Phaseolus vulgaris), lupine (Lupinus termis), cowpea (Vigna sinensis), chickpea (Cicer arietinum) and pea (Pisum sativum) under different environmental conditions throughout the World (Tseng et al 1995;Ruiz et al 1996;El-Nagerabi and Elshafie 2000;Kritzinger et al 2003;Castillo et al 2004;Kumar et al 2004;Domijan et al 2005;Embaby and Abdel-Galil 2006;Attitalla et al 2010). Fusarium semitectum, F. graminearum, F. chlamydosporum, F. equiseti, F. proliferatum and F. subglutinans were the most dominant fungal species in the seeds of Phaseolus vulgaris and Vigna sinensis from Argentina and South Africa (Castillo et al 2004;Kritzinger et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Mould was carried out according to their micromorphological properties using mould determination keys [3,4,9,11,12].…”
Section: Methodsmentioning
confidence: 99%